JUSTIFICATION FOR THE SUBJECT OF CONGRUENCE AND SIMILARITY IN THE CONTEXT OF DAILY LIFE AND CONCEPTUAL KNOWLEDGE - Sefa Dundar; Nazan Gunduz (Journal on Mathematics Education, 2017)
This study aims to examine prospective elementary mathematics teachers' conceptual knowledge level for congruence and similarity in triangles subject and to examine their ability to represent the knowledge, to associate the knowledge with daily life, and to justify and solve the geometry problems about this subject. The study is designed in a characteristic pattern. Total of 46 prospective elementary mathematics teachers were selected using purposive sampling method. The instruments used to collect data in this study are: GJP (Geometry Justification Problems), GCKQ (Geometry Conceptual Knowledge Questions) and GQDLE (Geometry Questions of Daily Life Examples). The data were analyzed using descriptive statistics method. The results of the study show that 1) the prospective teachers are successful in geometry conceptual knowledge questions but had difficulty in the justification problems; 2) there is a relationship between the theoretical knowledge levels and the argument standards of the prospective teachers; 3) the prospective teachers had difficulty in the daily life examples of congruence and similarity in triangles subject.Keywords: Congruence and Similarity, Justification, Conceptual Knowledge, Daily Life Association